MENGEMBANGKAN KEMAMPUAN LITERASI DAN BERFIKIR KRITIS SISWA MELALUI PEMBELAJARAN SASTRA BERBASIS KONTEKS - Balfas, Anwar (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract The teaching of literature in so far is still difficult and fear of the students and teacher. But the teaching of literature should actually be pleasant, challenging and exciting. The literature teaching condition which doesn’t close the students to the literary works make them blind on novels, short stories and poetries and drama. The students’ difficulty in understanding academic concepts taught by teachers results in the problems in encouraging and motivating students to learn. Those facts stimulate the shifting from the existing condition of literature teaching model into contextual literature teaching model. The five of the contextual literature teaching models are relating, experiencing, applying, cooperating and transferring. The purpose of these teaching models is to apply learning experiences for practical uses and needs. For practical uses, many ways that the teacher can create to make students apply and experience their creativity. They, for instance, may be encouraged to create literary work by their own, such as creating and performing drama, writing short stories and poems. The result of students’ creativities in literature may be followed by other activities such as exhibitions, fleet or publishing on school magazines, even they could be joined in literature writing competition.